Flexible Thermoelectrics: High‐Performance Flexible Bismuth Telluride Thin Film from Solution Processed Colloidal Nanoplates (Adv. Mater. Technol. 11/2020). Issue 11 (10th November 2020) - Hollar, Courtney; Lin, Zhaoyang; Kongara, Madhusudan; Varghese, Tony; Karthik, Chinnathambi; Schimpf, Jesse; Eixenberger, Josh; Davis, Paul H.; Wu, Yaqiao; Duan, Xiangfeng; Zhang, Yanliang; Estrada, David
Abstract : In article number 2000600, David Estrada and co‐workers demonstrate a low‐cost and room temperature method of producing colloidal thermoelectric nanoplatelets for scalable manufacturing of thermoelectric energy harvesters. This solution‐based approach is compatible with spin coating and aerosol jet printing, highlighting a wide range of thin film fabrication methods compatible with flexible polymer substrates. The thin films exhibit one of the highest reported peak power factors for solution processed thermoelectric materials. (Image credit: Alex Jerez).